Game Analysis of Product Supply Chain Considering Lead Time Compression and Demand Forecast Information Updating - Lemoine, Bizimana (International Journal of Accounting and Financial Reporting, 2023)
In a supplier-led decentralized decision-making second-level supply chain, consideration can compress lead times and update demand forecast information. This paper discusses the order volume decision of the retailer and the lead time and wholesale price decision of the supplier, analyzes the interaction between the retailer and the supplier’s decision and the influence of the cost of lead time reduction on the retailer and the supplier’s decision. The results show that the optimal order quantity of retailers is low in equilibrium, which leads to the service level of supply chain is less than 50% and the lead time of supply chain is too long. Encouraging retailers to increase order quantity is the key to improve supply chain service level and reduce supply chain lead time. Reducing the lead time and reducing the cost can not only enable retailers to increase the order quantity, improve the service level of the supply chain to the market demand, but also enable suppliers to reduce the order lead time and improve the response speed of the supply chain to the market demand.